Exosomal miRNA-215-5p Derived from Adipose-Derived Stem Cells Attenuates Epithelial–Mesenchymal Transition of Podocytes by Inhibiting ZEB2 - Jin, Juan (Biomed Res Int, 2020)
BACKGROUND: Podocyte migration is actively involved in the process of podocyte loss and proteinuria production, which is closely associated with the development of diabetic nephropathy (DN). Exosomes from adipose-derived stem cells (ADSCs-Exos) effectively inhibit podocyte apoptosis in the treatment of DN. However, how ADSCs-Exos affect the migration of podocytes is obscure. This study is aimed at exploring the regulatory role of ADSCs-Exos on cell migration and the underlying mechanism. METHODS: ADSCs-Exo was authenticated by transmission electron microscopy (TEM), western blotting, and flow cytometry. Cell viability and migration ability of podocytes were measured by CCK8 and Transwell assays, respectively. Relative expressions of miRNAs and mRNAs were determined by qRT-PCR. The transmitting between PKH26-labeled exosome and podocytes was evaluated by IF assay. Dual luciferase reporter assay was employed to detect the relationship between miR-215-5p and ZEB2. RESULTS: The exposure to serum from DN patient (hDN-serum) significantly inhibited cell viability of podocytes, but ADSCs-Exo addition notably blunts cytotoxicity induced by the transient stimulus of hDN-serum. Besides, ADSCs-Exo administration powerfully impeded high glucose- (HG-) induced migration and injury of podocyte. With the podocyte dysfunction, several miRNAs presented a significant decline under the treatment of HG including miR-251-5p, miR-879-5p, miR-3066-5p, and miR-7a-5p, all of which were rescued by the addition of ADSCs-Exo. However, only miR-251-5p was a key determinant in the process of ADSCs-Exo-mediated protective role on podocyte damage. The miR-251-5p inhibitor counteracted the improvement from the ADSCs-Exo preparation on HG-induced proliferation inhibition and migration promotion. Additionally, miR-215-5p mimics alone remarkably reversed HG-induced EMT process of podocyte. Mechanistically, we confirmed that ADSCs-Exos mediated the shuttling of miR-215-5p to podocyte, thereby protecting against HG-induced metastasis, possibly through inhibiting the transcription of ZEB2. CONCLUSION: ADSCs-Exo has the protective effect on HG-evoked EMT progression of podocytes thru a mechanism involving ZEB2. Potentially, the ADSCs-Exo preparation is a useful therapeutic strategy for improving podocyte dysfunction and DN symptoms clinically.